Latin America and the concentration of multi-systemic growth. Thesis and illustration of a social structural tendency - Alvear, Rafael (Revista de Sociología, 2023)
The diagnosis that Latin America stands as one of the most unequal continents in the world has become a phrase on everyone's lips. Although the approaches to inequalities and intersectionality have sought to broaden this analysis, highlighting the variety of deficiencies in broad parts of society, the problem of the excessive prosperity of extremely minority groups of the population has not yet received special attention. Based on this premise, this article aims to offer a new analytical perspective to understand the deployment of a structurally exacerbated inequality process, paradigmatically visible in this area of the world. Drawing on a sociological review and expanding on the contributions of Karl Marx and Pedro Vuskovic, the text appeals to a general tendency towards a concentration of access to the fruits of society's growth by minority groups of the population, considering not only the economy but also the totality of social systems. Along with the theoretical framework, the article provides an empirical illustration based on secondary statistical material to verify the concrete forms that this concentration acquires within each social system. Finally, the article offers reflections on the general panorama of concentration as it relates to the Latin American region.